Using Short-Term Concentration Measures and Intelligence in Rehabilitation Settings - Bruce D. Kirkcaldy (The Scientific World Journal)
Psychological assessment of cognitive functioning among clinical groups that include psychiatric and geriatric patients is a difficult task. This study examines the interrelationship between intelligence and concentrative ability for a group of psychiatric patients. Intellectual and concentrative ability were assessed among a group of 85, predominantly schizophrenic, patients (mean age 32 years) from a Sheltered Workshop (GWN) and neurological-psychiatric institutionalized care units within the Neuss region of North-Rhine Westphalia, Germany. Moderate bivariate relationships were found between all IQ subtests and the concentration performance variables (d2). A substantial overlap in variance was found between “nonverbal” intelligence and the concentration variables (using multiple regression and discrimination analysis). Error rate on the concentration task was significantly negatively correlated with the IQ variables, the magnitude of the correlation coefficient increasing as a function of the time on the task. Future studies would benefit from comparisons in factor structure similarity between abnormal and normal groups as well as between-clinical groups. At a practical level, the relatively easy use (less complex administration) and less obtrusive (hence, low level of personal threat) and inexpensive procedures of the letter cancellation task makes it a useful, albeit “approximate”, measure of cognitive functioning.